а)2sin²x-3sinx-2=0
Замена sinx=t
2t²-3t-2=0
D=3²+4×2×2=25
t₁= 3+√D÷4=3+5÷ 4=8÷4=2
t₂=3-√D÷4=3-5÷4=-2÷4=-0,5
Возвращаемся к замене
sinx=2 sinx=-0,5
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
4cos²x+4sinx-1=0
cos²x=1-sin²x
4( 1-sin²x)+4sinx-1=0
4-4sin²x+4sinx-1=0
-4sin²x+4sinx-1+4=0
-4 sin²x+4sinx+3=0 ÷(-1)
4sin²x-4sinx-3=0
Замена sinx=t
4t²-4t-3=0
D=4²+4×4×3=16+48=64
t₁=4+√D÷8= 4+8÷8=12÷8=1,5
t₂=4-√D÷8=4-8÷8= -4÷8=-0,5
Возвращаемся к замене
sinx=1,5 sinx=-1\2
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
x=5
x= - 1,5
Объяснение:
(2x/(x+2)+4/(x+2)(x+3)-3/(x+3)):(2x-1)+x/(3+x)=1
приводим к общему знаменателю
((2x(x+3)+4+3(x+2))/(x+2)(x+3)):(2x-1)/3+3/(3+x)=1
(2x^2+9x+10/(x+2)(x+3))•3/(2x-1)+3/(3+x)=1
(x+2)(2x+5)/(x+2)(x+3)•3/(2x-1)+3/(3+x)=1
(2x+5)3/(x+3)(2x-1)+3/(3+x)=1
6x+15+3(2x-1)/(x+3)(2x-1)=1
12x+12=2x^2+5x-3
2x^2-7x-15=0
D=49+120=169=13^2
x=(7+-13)/4
x=5
x=-1,5